Changes in Brain Transcripts Related to Alzheimer’s Disease in a Model of HFE Hemochromatosis are not Consistent with Increased Alzheimer’s Disease Risk - Johnstone, D.; Graham, Ross; Trinder, D.; Riveros, C.; Olynyk, John; Scott, R.; Moscato, P.; Milward, E. (IOS Press, 2012)
Iron abnormalities are observed in the brains of Alzheimer's disease (AD) patients, but it is unclear whether common disorders of systemic iron overload such as hemochromatosis alter risks of AD. We used microarrays and real-time reverse transcription-PCR to investigate changes in the brain transcriptome of adult Hfe−/− mice, a model of hemochromatosis, relative to age- and gender-matched wildtype controls. Classification by functional pathway analysis revealed transcript changes for various genes important in AD. There were decreases of up to 9-fold in transcripts for amyloid-β protein precursor, tau, apolipoprotein E, presenilin 1, and various other γ-secretase components, as well as Notch signaling pathway molecules. This included decreased transcripts for ‘hairy and enhancer of split’ Hes1 and Hes5, downstream targets of Notch canonical signaling. The reductions in Hes1 and Hes5 transcripts provide evidence that the changes in levels of transcripts for γ-secretase components and Notch signaling genes have functional consequences. The effects appeared relatively specific for AD in that few genes pertaining to other important neurodegenerative diseases, notably Parkinson's disease and Huntington's disease, or to inflammation, oxidative stress, or apoptosis, showed altered transcript levels. The observed effects on AD-related gene transcripts do not appear to be consistent with increased AD risk in HFE hemochromatosis and might, if anything, be predicted to protect against AD to some extent. As Hfe−/− mice did not have higher brain iron levels than wildtype controls, these studies highlight the need for further research in models of more severe hemochromatosis with brain iron loading.